Stretch to win : flexibility for improved speed, power, and agility - Frederick, Ann, ....-; Frederick, Chris, ....- (Champaign : Human Kinetics, 2017)
Are you looking for the key to optimal performance? Increased speed, power, and agility? What you need is a complete flexibility training system—one designed for today's athlete and made up of dynamic stretches that mirror sport-specific movement. And you should also have the skills to assess exactly what your body needs at any time. That complete program is found in Stretch to Win. In its first edition, Stretch to Win raised the bar for flexibility training. The first edition quickly became a best-selling stretching resource for consumers and professionals alike. From amateur to professional athletes, weekend warriors to Olympians, the benefits were clear: increased mobility, improved range of motion, faster recovery, and more. Now it's time to raise the bar further. This is Stretch to Win, Second Edition. Inside, Ann and Chris Frederick build on their system with the latest research, specific ways to assess yourself, and more stretching options. New illustrations of the body's fascia will help you assess and identify your imbalances. Then the text will guide you to eliminate these imbalances with corrective stretch movements that quickly improve mobility. You'll learn the most effective techniques for your sport, your position, or your event; then you'll put these techniques into action. Using the new Stretch to Win fascia mobility assessment (FMA) protocol, you'll determine range of motion deficits and identify your performance inhibitors. Then, with the stretching matrix, you'll personalize a program developed for your needs and your goals. You can incorporate the matrix into your existing workout as well as into rest days, when stretching can aid in recovery and bring your body back in balance. It's all here—all the tools, all the stretches, and all the instruction to create an effective flexibility program for any sport or activity.
Chapter 1 Ten Principles for Optimal Flexibility Chapter 2 Anatomy and Physiology of Flexibility Chapter 3 Flexibility Training Chapter 4 Flexibility for Sport Performance Chapter 5 Flexibility Assessment Chapter 6 Stretches for Optimal Mobility Chapter 7 Stretches for Sport-Specific Fascial Nets Chapter 8 Assisted Fascial Net Stretches
Keywords: Stretching